Indicionário do contemporâneo - Rocha, Aline (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2018)
Resenha de: CÁMARA, Mario; KLINGER, Diana; PEDROSA, Celia; WOLFF, Jorge (org.). Indicionário do contemporâneo. Belo Horizonte: UFMG, 2018.